Structuring customary marine courts to achieve legal certainty in the settlement of customary marine disputes - Suriyani, Meta; Ulya, Zaki; Hayati, Vivi; Fuadi, Fuadi (Jurnal Geuthèë: Penelitian Multidisiplin, 2024)
The aim of this study is to build legally and socially independent Panglima laot and fisher community groups to resolve adat laot issues through adat laot courts, and to increase community empowerment in the area of services in social conflicts in fishing communities. Panglima laot lhok Idi Rayeuk in Alue Dua Muka O village in resolving disputes between fishermen and violations of customary maritime law, where there is still confusion in its application. The existing guidelines for customary courts in Aceh are considered to be very general and only discuss gampong customary courts. Meanwhile, the laot customary court has not yet specified its implementation mechanism. The Laot Customary Court and the Gampong Customary Court have different resolutions, and the customary institutions that resolve them are also different. So that it has the potential to conflict with positive law and tends to be neglected and protracted in handling. This is due to the lack of understanding of the Panglima Laot Lhok of the laot customary judicial process. The activity methods used were (1) observation, advice and discussion; (2) training and mentoring; and (3) activity evaluation. The results of the activities showed that the education and training provided in relation to Laot customary justice resulted in changes in the attitudes and knowledge of the target audience (partner group) of Panglima Laot Lhok and fishing communities towards the implementation and structuring of Laot customary justice as a means of seeking justice in resolving Laot customary disputes. This training has also provided an understanding of the rule of law as a foundation, the benefits as an alternative to solving problems with the aim of peace (win-win solution), the implementation process to achieve common goals of justice and order